Deed, Thought, and Word of Alexey Nikolaevich Leontiev - Antonina N. Zhdan; Elena E. Sokolova (Lomonosov Moscow State University, 2023)
Background. The article presents the most important events in the scientific biography of A.N. Leontiev (1903-1979). Some aspects of his psychological theory of activity are being analyzed. The relevance of addressing the heritage of A.N. Leontiev and his scientific school is determined by the implemented methodology of psychological research, which is an alternative to the approaches to the study of consciousness that dominate in modern world science. Objectives of the paper were to highlight those aspects of psychological theory of activity that were successfully implemented in "highly organized practice" as well as to discuss some controversial issues of cultural-activity psychology. Method. Well-known works of Leontiev, his colleagues, and opponents served as sources for the study, historical and psychological in genre and methodology. Some archive materials, including those that have not been previously introduced to scientific comunity were used as well. Results. A new solution to the problem of the relation between Word and Deed, which was debated by L.S. Vygotsky and A.N. Leontiev and is still being debated in the modern literature, is proposed. It is stated that Leontiev's doctrine on the forms of connection between meanings and senses in the structure of consciousness was included in the methodological foundations of "pedagogy of freedom", seeking to develop a culture of thinking and personal growth in students. The examples of the realization of this pedagogy in teaching students at the Faculty of Psychology of Moscow State University are presented. Studying personal letters from the family archives provided some new details about Leontiev's administrative and organizational activities during the Great Patriotic War. Conclusion. The immediate tasks of the historical and psychological study of Leontiev's contribution are to: 1) analyze the empirical research of his school in the 1940s and the following years; 2) study systematically the contribution of this school to practical psychology; 3) create a complete and detailed chronology of A.N. Leontiev's life and work; 4) develop teaching aids for psychology students with the explanation of the complex issues and contradictions in A.N. Leontiev's activity theory as well as with scientific comments on his works, within the sociocultural context of their creation.